A critical analysis of “Si dovrebbe pensare più a far bene... Alessandro Manzoni: Il progetto di Dio, il lavoro dell'uomo” - Fatemeh Asgari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In a large bibliography like those of Alessandro Manzoni each monograph presented by his philologist should definitely be considered for its "new critical point of view” with which the author of the study wanted to contribute to a series of long observations and various reflections on Manzoni as a writer and as a thinker. The volume of essays by Norberto Cacciaglia is particularly interesting for how  author manages to invite the reader's attention to the new historical details of Manzoni’s masterpiece I PromessiSposi,  highlighting unusual insights not always easily traceable if not through a new point of view. The work of Cacciaglia is different because of how he emphasizes the value of working and the law of the economy in the PromessiSposi’s historical society.